Transfering Technology to Farmers – DMR shows the way - Yadav, Virendra Kumar (Indian Farming, 2015)
Maize technologies are being transferred from lab to field in collaboration of public (AICRP centres on maize, Krishi Vigyan Kendras, state Department of Agriculture, etc.) and private sector organizations (eg. private seed companies, NGOs, farmers’ group, etc.) through various extension methods. National productivity of maize is gradually increasing through adoption of improved technologies by farmers. More efforts should be given on public extension so that poorest of the poor, farmers in tribal areas, hilly areas, neglected areas, etc. would also be benefitted through available technologies. There is need to work hand in hand with all partners (e.g. seed companies, NGOs, researchers, farmers etc.) of technology dissemination for increasing maize production, removing hunger and malnutrition, generating employment opportunities and augmenting income level of farmers.